Setting the top 10 research priorities to improve the health of people with Type 2 diabetes: a Diabetes UK–James Lind Alliance Priority Setting Partnership - Finer, S; Robb, P; Cowan, K; Daly, A; Shah, K; Farmer, A (John Wiley & Sons Ltd, 2018)
Aims To describe processes and outcomes of a priority setting partnership to identify the ‘top 10 research priorities’ in Type 2 diabetes, involving people living with the condition, their carers, and healthcare professionals. Methods We followed the four‐step James Lind Alliance Priority Setting Partnership process which involved: gathering uncertainties using a questionnaire survey distributed to 70 000 people living with Type 2 diabetes and their carers, and healthcare professionals; organizing the uncertainties; interim priority setting by resampling of participants with a second survey; and final priority setting in an independent group of participants, using the nominal group technique. At each step the steering group closely monitored and guided the process. Results In the first survey, 8227 uncertainties were proposed by 2587 participants, of whom 18% were from black, Asian and minority ethnic groups. Uncertainties were formatted and collated into 114 indicative questions. A total of 1506 people contributed to a second survey, generating a shortlist of 24 questions equally weighted to the contributions of people living with diabetes and their carers and those of healthcare professionals. In the final step the ‘top 10 research priorities’ were selected, including questions on cure and reversal, risk identification and prevention, and self‐management approaches in Type 2 diabetes. Conclusion Systematic and transparent methodology was used to identify research priorities in a large and genuine partnership of people with lived and professional experience of Type 2 diabetes. The top 10 questions represent consensus areas of research priority to guide future research, deliver responsive and strategic allocation of research resources, and improve the future health and well‐being of people living with, and at risk of, Type 2 diabetes.